Strategic Analysis of the Reasons for the Delay of the Investment Projects of the North Oil Company / Case Study - سعيد عبد السلام لفته; محي الدين شيماء عبد الكريم (Journal of Economics and Administrative Sciences, 2019)
The research aims to find a contemporary model in analyzing the reasons behind the delay of the investment plan projects suffered by the North Oil Company. This model is able to understand the environment surrounding the implementation of projects in the light of the changes facing the company at the present time, which in turn requires the need to identify the most important strengths and weaknesses Internal and external opportunities and threats using the SWOT matrix and identify the appropriate strategic alternative based on clear policy, strategies and programs to address weaknesses and look to the future prospects as the company can be stronger and more flexible environmental changes surrounding the reality of implementation Investment plan projects, because the strategic analysis is the best way out of the stalemate and stability to the circle of innovation and creativity, the implementation of those projects of importance in the economic development of the country. The research community of the investment projects of the North Oil Company and approved by the Ministry during the period (2013-2017), the number of projects (279) projects distributed on (11) major project, and classified into completed projects and by (5.7%) This is indicative of a high degree of delay and delay in the implementation of the projects of the company’s investment plan (94.3%). It was concluded that the process of strategic analysis is an important step for the company to detect the internal and external environment to address the current and future weaknesses and threats to the projects and a good way to draw the factors of success and the formulation of programs and strategies as a preventive and remedial, and that internal weaknesses are affecting the completion of the investment plan projects of the company, Therefore, the researcher recommended the adoption of the proposed program in the current study, directed at the internal and external environment, in order to achieve the goals and objectives through the development of fields and expand the performance of production facilities and increase production capacity and For the export of crude oil and gas to the company.